2009
DOI: 10.3136/fstr.15.453
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxin Toxicity in Saccharomyces cerevisiae Differs Depending on Gene Mutations

Abstract: Mycotoxin inhibits the growth of Saccharomyces cerevisiae mutants with disrupted stress response genes, but no that of wild type yeast even at high concentrations. The S. cerevisiae genome database (SGD) project has recently generated many gene disruptants, including those with disrupted stress responseassociated genes. The present study examined the relationship between mycotoxicity and the disruption of functional yeast genes, especially those involved with stress responses. Growth tests showed a major impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
0
18
1
Order By: Relevance
“…Analysis of global microarray changes in S. cerevisiae exposed to patulin showed that many genes involved in detoxification processes, oxidative stress response, and DNA repair are highly induced (30). In another study, a genetic correlation in patulin-and oxidative-stress-susceptible strains of S. cerevisiae was found, indicating a mechanistic similarity between patulin toxicity and oxidative stress (78). In agreement with these studies, we found that 10 of 13 (77%) patulin-sensitive strains were also highly sensitive to at least one oxidative-stress-inducing agent, and 6 (46%) (mutants pac2 and dal5, transformants 123a, GIS5, 954a, and 18a) exhibited hypersensitivity to all ROS or ROSgenerating compounds ( Fig.…”
Section: Figmentioning
confidence: 91%
“…Analysis of global microarray changes in S. cerevisiae exposed to patulin showed that many genes involved in detoxification processes, oxidative stress response, and DNA repair are highly induced (30). In another study, a genetic correlation in patulin-and oxidative-stress-susceptible strains of S. cerevisiae was found, indicating a mechanistic similarity between patulin toxicity and oxidative stress (78). In agreement with these studies, we found that 10 of 13 (77%) patulin-sensitive strains were also highly sensitive to at least one oxidative-stress-inducing agent, and 6 (46%) (mutants pac2 and dal5, transformants 123a, GIS5, 954a, and 18a) exhibited hypersensitivity to all ROS or ROSgenerating compounds ( Fig.…”
Section: Figmentioning
confidence: 91%
“…In detail, activation of the MAPK cascade is related to conditions of high osmolarity response and cell integrity, and is negatively regulated by Ptc1 [12] [13]. With the loss of Ptc1 function, the cell wall of ptc1Δ is loosened, and the sensitivity to mycotoxin is increased by SDS [10] [11]. A previous study also reported that fumonisin B 1 (FB 1 ) activates MAPK [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the MAPK cascade is influenced by cancer [9], leading to the possibility that AFB 1 -derived toxicity can be observed through MAPK-related genes. We previously reported that yeast PTC1 gene disruptant (ptc1Δ) is sensitive to both DON and AFB 1 with low concentrations of sodium dodecyl sulfate (SDS) [10]. PTC1 encodes Ser/Thr phosphatase 2C, which is involved in cell wall β-1,3-glucan assembly and is a negative regulator of the MAPK cascade [11].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, PDR5, which encodes a protein that acts in the multidrug resistance system [28], was the only multidrug resistance category gene found in both the present study and the report by Sirisattha [24]. We previous reported that the PDR5 mutant strain shows high susceptibility to both DON and T-2 toxin [13], suggesting that the PDR5 coding protein strongly influences the elimination of trichothecene mycotoxin. Several similar results have already been reported [29] [30].…”
Section: Discussionmentioning
confidence: 74%
“…We reported that the yeast (Saccharomyces cerevisiae) PTC1 mutant strain (ptc1) has a high susceptibility to certain mycotoxins, such as aflatoxin B 1 (AFB 1 ), DON, T-2 toxin (T-2), and patulin, with a low sodium dodecyl sulfate condition [13]. Yeast PTC1 encodes a serine/threonine phosphatase that negatively affects the interaction between MAPK and MAPKK in the HOG pathway, which regulates responses to high osmolarity [14][15] [16] [17].…”
Section: Introductionmentioning
confidence: 99%